2003
DOI: 10.1097/00008877-200302000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Morphine state-dependent learning: interactions with α2-adrenoceptors and acute stress

Abstract: The interactions of -adrenoceptors and acute restraint stress with morphine state-dependent memory of passive avoidance were examined in mice. Memory acquired following pre-training morphine administration (5 mg/kg, i.p.) was dose- and time-dependently retrieved by pre-test morphine; this effect was reversible by yohimbine (1 mg/kg). Pre-test clonidine (0.005-0.1 mg/kg) was also effective in restoring morphine-induced memory. Pre-training clonidine (2 mg/kg) induced an amnestic effect that was restorable by pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 60 publications
4
30
0
1
Order By: Relevance
“…Each 500-s-long daily session consisted of trials separated by intertrial intervals (ITIs) of variable duration, averaging 15 s. During the 8 d of training, selected groups of mice were exposed to stress before each daily session. On training days 3, 6 and 8, different groups of mice were treated with adrenergic alpha-2 receptor drugs clonidine and yohimbine, which affect brain norepinephrine levels 28 . During the 5 d of recall, we asked whether mouse performance was most influenced by current stress or by memories of stress experienced during training.…”
Section: Resultsmentioning
confidence: 99%
“…Each 500-s-long daily session consisted of trials separated by intertrial intervals (ITIs) of variable duration, averaging 15 s. During the 8 d of training, selected groups of mice were exposed to stress before each daily session. On training days 3, 6 and 8, different groups of mice were treated with adrenergic alpha-2 receptor drugs clonidine and yohimbine, which affect brain norepinephrine levels 28 . During the 5 d of recall, we asked whether mouse performance was most influenced by current stress or by memories of stress experienced during training.…”
Section: Resultsmentioning
confidence: 99%
“…In animals, clonidine has been found to produce memory impairments in several learning paradigms ranging from shuttle box (Hawkins and Monti, 1979;Homayoun et al, 2003) to avoidance tasks (Galeotti et al, 2004;Genkova-Papasova and Lazarova-Bakurova, 1988;Genkova-Papazova et al, 1997) and to cue detection (Smith and Aston-Jones, 2011;Brown et al, 2012). Some studies in humans have also reported memory impairments associated with clonidine administration in healthy subjects (Riekkinen et al, 1999;Hall et al, 2001) and in Alzheimer's disease patients (Jakala et al, 1999a, b).…”
Section: Dosage and Number Of Treatmentsmentioning
confidence: 99%
“…Additionally, a few open-label studies have shown beneficial effects of clonidine in treating some PTSD symptoms (Kinzie and Leung, 1989;Harmon and Riggs, 1996;Ziegenhorn et al, 2009), but none of these studies used clonidine specifically in combination with traumatic memory retrieval. In animal models, the use of clonidine has been found to produce memory impairments in step-down (GenkovaPapasova and Lazarova-Bakurova, 1988;Genkova-Papazova et al, 1997), shuttle box (Hawkins and Monti, 1979;Homayoun et al, 2003), and passive avoidance tasks (Galeotti et al, 2004); however, the use of clonidine to block memory reconsolidation has yet to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Our results are consistent with studies showing that clonidine has detrimental effects on memory. In animals, clonidine has been found to produce memory impairments in several learning paradigms ranging from shuttle box (Hawkins and Monti, 1979;Homayoun et al, 2003) to avoidance tasks (Galeotti et al, 2004;Genkova-Papasova and Lazarova-Bakurova, 1988;Genkova-Papazova et al, 1997) and to cue detection (Smith and Aston-Jones, 2011;Brown et al, 2012). Some studies in humans have also reported memory impairments associated with clonidine administration in healthy subjects (Riekkinen et al, 1999;Hall et al, 2001) and in Alzheimer's disease patients (Jakala et al, 1999a, b).…”
Section: Dosage and Number Of Treatmentsmentioning
confidence: 99%
“…Additionally, a few open-label studies have shown beneficial effects of clonidine in treating some PTSD symptoms (Kinzie and Leung, 1989;Harmon and Riggs, 1996;Ziegenhorn et al, 2009), but none of these studies used clonidine specifically in combination with traumatic memory retrieval. In animal models, the use of clonidine has been found to produce memory impairments in step-down (GenkovaPapasova and Lazarova-Bakurova, 1988; Genkova-Papazova et al, 1997), shuttle box (Hawkins and Monti, 1979;Homayoun et al, 2003), and passive avoidance tasks (Galeotti et al, 2004); however, the use of clonidine to block memory reconsolidation has yet to be investigated.…”
Section: Introductionmentioning
confidence: 99%